Pengaruh Moral Disengagement terhadap Perilaku Cyber Aggression pada Peserta Didik - Laraswati, Reki; Moesarofah, Moesarofah (Universitas PGRI Kanjuruhan Malang, 2024)
The digital era has brought significant changes in socializing and association, especially among young adolescents. Unfortunately, along with it, negative trends have emerged, such as cyber aggression, which is influenced by the level of moral disengagement of students in justifying their detrimental behavior online. This study aims to analyze the influence of moral disengagement on cyber aggression behavior. The research approach used is quantitative, with a cross-sectional design. The sampling technique used simple random sampling. The research participants were 9th grade students at UPT SMPN 29 Gresik, totaling 130 people. Data collection used a moral disengagement and cyber aggression scale. Data analysis used a simple linear regression test technique. The results of the study showed that there was an influence of moral disengagement on cyber aggression of 22.8% with a significance level of 0.000 <0.05. The implications of the study indicate the importance of preventive efforts for cyber aggression behavior by providing education on digital ethics and healthy use of social media.